ORGANIZATION OF THE PLAY SPACE AS A FACTOR IN THE DEVELOPMENT OF PRESCHOOL CHILDREN’S PERSONAL POTENTIAL - Bondar, Oksana (Personality and environmental issues, 2025)
The article examines the theoretical and methodological foundations of the organization of play space for preschool children and its impact on the development of personal potential. The play space is considered as a complex system of conditions that combines social, psychological and subject-spatial aspects of child development, creates opportunities for the manifestation of independence, initiative, creative activity and the formation of social skills. It has been shown that a well-organized play space promotes the development of cognitive abilities, cognitive motivation, emotional intelligence, moral guidelines and self-awareness of preschoolers, influences the development of individual capabilities of the child in various spheres of human existence, the formation of internal freedom, independence and responsibility in relations with the social and natural environment. It has been found that the modern organization of preschoolers' play space should provide a holistic approach to the preservation and strengthening of the child's physical, mental, social and spiritual health. It is proved that the implementation of a child-centered approach to creating a play space involves not only providing the child with the opportunity to be an active subject of his or her own play activities, but also modeling conditions that stimulate initiative, self-expression and awareness of their own capabilities. The article presents the results of a focus group survey of preschool educators, which showed that in real practice the organization of play space often does not meet its potential as a means of personal development; there is a limited variability of children's activities, insufficient consideration of individual needs and activity of preschoolers. It is stated that the design of the play space is a continuous process and a multi-level system of actions aimed at creating a reflective and developmental environment in preschool education institution, in which the child has the opportunity to freely choose activities, move between them, as well as develop flexibility, openness and partnership with adults and peers. This makes it possible to take into account the dynamics of preschool children's needs in creating a quality developmental environment and find the best ways to meet them. The need to take into account the age, social and psychological characteristics of children, as well as zoning, mobility and variability of the environment of preschool education is emphasized. The play space within the framework of story-role, imaginative-role and productive games forms social, communicative, emotional and cognitive competencies, prepares children for school and promotes their adaptation in the social environment. It has been determined that promising areas for further research are the study of the impact of the quality of the play space on the development of individual characteristics, cognitive and intellectual abilities, creativity and creativity of preschoolers, as well as on their readiness for schooling and successful adaptation.